WHERE HAS ALL THE PUNCTUATION GONE? OF CULPRITS, VICTIMS AND CASUALTY - Mokgwathi, Tsaona; Otlhomile, Boitshoko (PEOPLE: International Journal of Social Sciences, 2017)
This paper investigates the root cause of little or lack of punctuation in writing. The researchers as teachers of writing for many years at different institutions have realised that students have little or no regard for the use of punctuation in writing, yet punctuation is one of the most important aspects when writing both in English as the Language of Instruction in education and in Setswana as the national language. Punctuation gives meaning to the written words, and that its omission or wrong use may convey a different meaning from the one the writer intended, or may render the writing altogether meaningless. The study was conducted at a university of science and technology and it involved first year students enrolled in four engineering programmes. The first year classes were chosen because it is the first stage into university education. The data were collected and analysed qualitatively. It is hoped that the results of the study will inform lecturers at tertiary institutions and teachers of secondary schools about the punctuation problems that students bring into the university. These problems have a negative effect on the quality of the students’ written work, and eventually, their academic performance. It is recommended that the students are sensitised about the importance of correct punctuation in writing. Consequently, lecturers of writing in tertiary education institutions will receive students who are better writers.